2020
DOI: 10.1007/s10726-020-09716-9
|View full text |Cite
|
Sign up to set email alerts
|

Who is Best at Mediating a Social Conflict? Comparing Robots, Screens and Humans

Abstract: The impacts of various mediation platforms on negotiation outcomes and perceptions are compared in this article. The mediator platforms contrasted were a (teleoperated) Telenoid robot, a human, and a computer screen. All of these platforms used the same script for process diagnosis, analysis, and advice on how to resolve an impasse in a simulated high-tech company de-merger negotiation. A fourth experimental condition consisted of a no-mediation control. More agreements and more integrative agreements were att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(68 reference statements)
0
10
0
1
Order By: Relevance
“…If the field of SHRI was to operate with more prominent and nuanced attention to novelty effects, then perhaps these proposals would equally contain an identification of robot novelty as an instigator of these outputs. In a study by Druckman et al (2021) , the authors reflect upon the possibility of positive robot effects on creative negotiation outcomes as brought on by robot novelty effects on participant abilities to engage in divergent or creative thinking. Considering the arguments presented in this paper, that novelty may disrupt established meaning-making and force the experiencee in generating alternative meaning, such a reflection seems justified.…”
Section: Four Reasons For Increasing Interdisciplinary Efforts On Nov...mentioning
confidence: 99%
“…If the field of SHRI was to operate with more prominent and nuanced attention to novelty effects, then perhaps these proposals would equally contain an identification of robot novelty as an instigator of these outputs. In a study by Druckman et al (2021) , the authors reflect upon the possibility of positive robot effects on creative negotiation outcomes as brought on by robot novelty effects on participant abilities to engage in divergent or creative thinking. Considering the arguments presented in this paper, that novelty may disrupt established meaning-making and force the experiencee in generating alternative meaning, such a reflection seems justified.…”
Section: Four Reasons For Increasing Interdisciplinary Efforts On Nov...mentioning
confidence: 99%
“…For example, a social robot can improve people's interpersonal conflict resolution skills by flagging a conflict onset and offering prompts for conflict resolution [43]. Mediation via the Telenoid robot was also found to produce more agreements and more integrative agreements among human teammates in comparison with both a screen mediator and a human mediator [6]. The last social role category that a robot often takes in a human group is a moderator/supporter role.…”
Section: Social Hri On Earth 21 Robot Social Roles In Human Groupsmentioning
confidence: 99%
“…However, barely any prior work focused on the design and impact of robot roles on the group dynamics and processes of space crew teams, posing a new urgency to investigate the nuanced challenges for social HRI in space. For example, a robot mediator has been empirically shown to resolve people's interpersonal conflicts more effectively than a screen mediator or a human mediator [6], but the design considerations for a robot mediation in astronaut-astronaut interactions remain unexplored. Understanding astronauts' perception, acceptance and needs of social robots in different LDSE-related interaction contexts would help design for more astronaut-centered HRI.…”
Section: Robot Social Role Designmentioning
confidence: 99%
“…In classes on negotiation, the first author uses a rubber band to illustrate the idea of stretching the frontier to the point where the band can no longer tolerate the tension. In a recent experiment, we found that the most creative agreements were those that reflected out‐of‐the‐box nonstructured solutions, usually obtained by robot mediators (Druckman et al 2021).…”
mentioning
confidence: 94%